Family Nursing Care with Family Health Management Problems is Ineffective in Handling Hypertension Elderly Through Family Support in the Work Area of the Rambipuji Health Center Jember Regency - Tantut Susanto; Muh. Ariandi Maulana; Naretta Khoirunisak; Risma Eka Putri Arlyani; Virgiana Piesesha; Melaniara Anggista; Trisya Aulia Damayanti (Journal of Health Community Service, 2026)
Background:, Family involvement is very important in maintaining the welfare and health of elderly members, especially in the elderly with hypertension. Family support can improve adherence to treatment of the elderly through monitoring and providing encouragement to individuals undergoing treatment. Method: a case study by providing nursing care to two assisted families for 3 weeks with health education interventions, progressive muscle relaxation therapy and slow stroke back massage therapy. Results and Discussion: The results showed a correlation of 0.000 and sig. (2. tailed) 0.049 which means that there is an effect of family support with health education about hypertension in both assisted families. The p-value of systolic blood pressure before and after ROP (p = 0.023) and the p-value of diastolic blood pressure before and after ROP (p = 0.038) indicated that there was an effect of family support through progressive muscle relaxation on blood pressure. p-value on systolic blood pressure before and after SSBM (p = 0.049) and p-value on diastolic blood pressure before and after SSBM (p = 0.049) thus indicating that there is an effect of family support through slow stroke back massage therapy on blood pressure. Conclusion: Implementation of nursing carried out through family support such as health education, progressive muscle relaxation therapy and slow stroke back massage can affect blood pressure in the elderly.